Proceedings. 2000 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS 2000) (Cat. No.00CH37113)
DOI: 10.1109/iros.2000.895316
|View full text |Cite
|
Sign up to set email alerts
|

High-level control of a mobile manipulator for door opening

Abstract: In this paper, off-the-shelf algorithms f o r force/torque control are used in the context of mobile manipulation (i.e. coordinated motion of a mobile robot base and the a r m mounted o n top of it). In particular, the task of opening a door is studied. To make the solution robust, as f e w assumptions as possible are made. B y using relaxation of forces as the basic level of control, more complex information can be derived f r o m the resulting motion. In our system, the radius and the centre of rotation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 7 publications
0
67
0
Order By: Relevance
“…Peterson et al [17] and Nagatani et al [18] developed force/torque control of a mobile manipulator to open a door. Alternatively, Chitta et al [19] showed how to overcome the high-dimensionality of the planning problem by identifying a graph-based representation that was small enough for efficient planning yet contained coordinated arm and base motions to open varying type doors.…”
Section: Experimental Applicationsmentioning
confidence: 99%
“…Peterson et al [17] and Nagatani et al [18] developed force/torque control of a mobile manipulator to open a door. Alternatively, Chitta et al [19] showed how to overcome the high-dimensionality of the planning problem by identifying a graph-based representation that was small enough for efficient planning yet contained coordinated arm and base motions to open varying type doors.…”
Section: Experimental Applicationsmentioning
confidence: 99%
“…In Peterson et al (2000), the recorded motion of the end-effector is used in a least-squares approximation algorithm in order to estimate the center and the radius of the motion arc while lowest level compliant control annihilates the effects of the high forces exerted due to inaccurate trajectory planning. An optimization algorithm using position of the end-effector has also been used in Kemp (2009, 2010); the algorithm obtains estimates of the radius and the center of the door trajectory and subsequently estimates of the control directions.…”
Section: Related Workmentioning
confidence: 99%
“…Related works on constrained manipulation in human environment often regard it as a planning problem, e.g. [5], [6], [7], [8]. These approaches require in general specific knowledge about the constraints, imposed by the manipulated objects, which makes them prone to modeling errors and uncertainties.…”
Section: Introductionmentioning
confidence: 99%